Little environmental dimension, gives reason to an urgent need and sustainable proposal of curricular inclusion - Solano, Dr. Ramón Bedolla; LogamurthieAthiemoolam, Dr.; Rosas, Dra. María Laura Sampedro (IJRDO- Journal of Educational Research, 2017)
The environmental crisis in the world, has promoted the integration of the environmental dimensionin education, in this area, are located universities. Resolutions of international summits such as theone organized by the United Nations in Johannesburg in 2002 led to the introduction of theEnvironmental Dimension in the educational field. Many educational institutions do not. Theresults of a research conducted in November 2015 at the Nelson Mandela Metropolitan University,School of Education in Port Elizabeth, South Africa, according to the objective "to identify theenvironmental in the curriculum and the need for its integration", showed that "environmental"does not included, and added to it, a proposal based on the curricular design that includes steps forits inclusion arises. The identification of the environmental, was determined through the results ofa survey that was previously reviewed and piloted and that covered the variables (environmentalproblems, curriculum and environmental competencies), this instrument was applied to the actorsof the educational process, study sample. The sample was given through a non-probabilisticapproach. It is determined, according to the problem identified, the need to implement theenvironment as a dimension in the curriculum.